Prognostic significance of positron emission tomography using fluorine-18-fluorodeoxyglucose in patients treated for malignant lymphoma - Cremerius, U.; Fabry, U.; Neuerburg, J.; Zimny, M.; Bares, R.; Osieka, R.; Bull, U. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: To evaluate the prognostic significance of positron emission tomography (PET) using fluorine-18-[2]-fluoro-2-deoxyglucose (FDG) in patients treated for Hodgkin’s disease (HD) or nori-Hodgkin’s lymphoma (NHL) compared to conventional restaging (CRS). Methods: Fifty-six patients with either HD (ç = 22), high-grade NHL (n = 26) or centrocyfic-centroblastic NHL (n = 8) were included. PET was performed in 41 patients for treatment reevaluation up to three months after therapy and in patients with persisting residual masses (n = 10) or suspected relapse (n = 5) four to twelve months after treatment. The scans were evaluated qualitatively and quantitatively using standardised uptake values (SUV). Progression-free survival (PFS) was estimated to assess the prognostic value of FDG PET and clinical follow-up was taken as gold standard. Results: PET was positive in nineteen of 41 patients studied for treatment reevaluation. Progression was observed after a median interval of two months (range 0-15) in sixteen of 19 patients after a positive PET scan and in three of 22 patients after a negative scan (p <.001). Median duration of follow-up in progression-free patients was 21 months (range 6-72). In patients with a partial remission in CRS progression was more common in PET-positive than in PET-negative patients (5 of 7 vs. 1 of 14; ñ <.01) and positivity with PET was associated with poorer PFS (p <.0025). PET studies performed four to twelve months after treatment were true negative in seven, true positive in five and false-positive in three patients. SUV > 11.35 of lymphoma lesions was associated with poorer PFS than SUV <11.35 (p <0.025). Conclusion: We conclude that FDG PET after treatment of malignant lymphoma has a high prognostic value and should be recommended in patients with persistence of residual masses.
Keywords: PET; FDG; malignant lymphoma; prognosis; residual mass